Baseline Study of Microplastics in the Gastrointestinal Tract of Commercial Species Inhabiting in the Coastal Waters of Karachi, Sindh, Pakistan - Akhter, Najeeb; Panhwar, Sher Khan (Frontiers in Marine Science, 2022)
Microplastic (MPs) emergence in the pelagic and mesopelagic species was carried out to delineate coastal degradation and ecosystem status around Karachi metropolis. The species of high commercial and ecological worth were sampled using gillnet of 1.5 cm, knot-to-knot mesh size in November and December 2021. In total twenty six individuals including Liza subviridis (15), Thryssa dussumieri (3), Rastrelliger kanagurta (2) and Portunus sanguinolentus (6) were used to perceive MPs. Strong linearity between body length and MPs (R2 = 0.928, SE 0.069 and R2 = 0.928, SE 0.104 were calculated for L. subviridis, P. sangiuilatus and respectively. However, data of T. dussummeiri and R. Kanagurta showed minimization failure. The MPs in GIT was extracted using direct observation under sophisticated binuclear microscope and chemically digestion (KOH) together with wet peroxide oxidation (H2O2+FeSO4) methods. The MPs stuffs were categorized as foam, film, fiber, fragment and bead of three different sizes 170, 120, 100 µm in stomach, intestine and esophagus. Frequently appeared sort of MPs was films whereas beads rarely seen. It is hoped that this underline research would help to minimize industrial release, recognize critical knowledge gaps, demonstrated MPs flux being released into the aquatic environment. The results will support mitigation of this emerging threat to the living resources around Karachi coastal area.